Culture, administration, reform in Africa - Hyden, Goran (2013)
Research on public administration in Africa has been prescriptive rather than analytical. Solutions have been provided in search of problems. Little, if any, attention has been paid to the role of local administrative cultures. This article problematizes public sector reform efforts on the African continent by identifying the cultural realities in which administration is being pursued and how the practices differ from the prescriptions offered by consultants. A principal distinction is made between a "civic" and an "affective" cultural model. The conclusion is that any reform efforts in the future need to start from what is on the ground rather than trying to impose something from outside that does not match existing administrative practices. - Reproduced.
Keywords: Public administration - Africa; Administrative reform - Africa; Administrative reform